The Placebo Effect and Learning: Implications for Counsellors - Hagen, Brad; Gunn, Thelma (Canadian Journal of Counselling and Psychotherapy, 2007)
English The placebo effect is a fascinating and complex phenomenon, and may well account for much of the effectiveness of many medical therapies, such as pain medications and antidepressants. While health professionals have long debated the role that placebos may play in health care, the counselling profession has devoted less attention to the placebo effect in counselling, despite claims that it may account for much of the effectiveness of counselling. The authors offer a brief overview of the placebo effect, review theoretical and learning perspectives on the placebo effect, summarize the arguments for and against the existence of a placebo effect in counselling, and conclude with implications for counsellors.Français Non disponible